First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations A New Departure At a meeting of the Joint Councils of the League the Bishop of Birmingham, Vice-President, expressed the opinion that addresses in Churches from below the chancel steps delivered by medical men and women on matters of Health would be of great value to the public, and invited members of the Lecture Staff of the League to consider the suggestion. At the invitation of Canon J.G. Rogers, Vicar of the Parish of West Ham, Mr. E.B. Turner, F.R.C.S., of the Medical Council of the League, will preach the sermon on Hospital Sunday, June 18th (evening service), at West Ham Parish Church. National Council of Mental Hygiene The League is desirous of working in close co-operation with the National Council of Mental Hygiene, which has just been inaugurated in this country, and to which it has offered the hospitality of its offices pending the establishment of the Council's own Headquarters. In the opinion of this League, the need of such a Council has long been felt. In July, 1921, a letter was received from Professor Giovanni Palastrelli, Minister of Agriculture, Rome, asking for details of the work of the League, and other social and health work in England, with which request the League complied. National Boarding Schools. In March, 1920, the subject of National Boarding Schools was brought before the Medical Council of the League by the Hon. Organiser, the idea submitted to its members being the value of taking from over-crowded slum districts children who would be recommended by Medical Inspectors of Council Schools as likely to benefit in health by being sent to the country or seaside, where certain of such schools would be located, thus, without interfering with their education, enabling delicate and sub-normal children to grow up healthy wage-earning citizens. The schools, it was suggested, should be supported partly by the State and partly by the parents. The motion from the Chair was that theoretically the idea was excellent, but practically impossible for the country's finances at the present time. The motion was carried. Birth Control. At a meeting held on November 6th, 1919, by the Medical Control Council, the matter of whether the League should deal with this subject in the Medical Pamphlets which it was publishing, it was decided to issue a pamphlet under the title of "Responsibility for Parenthood," to be written by Dr. Killick Millard, M.D., D.Sc., M.O.H. for Leicester. National Institute of Industrial Psychology The economic necessity for raising the standard of health of the people is ever before the minds of our Councils. We are working in close co-operation with the National Institute of Industrial Psychology, and hope to be even more closely allied. The League fully realises that future productiveness (which means the future success of a nation) depends upon two things, the health of its people and the elimination of waste in the industrial and commercial world. The fact that already 200 Institutes of Vocational Guidance and Selection already exist in the United States of America, three in Belgium and one in Barcelona, is being brought to the knowledge of the people of our country through lectures arranged by the League. League of Red Cross Societies at Geneva. In February, 1921, we received a request from this Society for copies of our literature dealing with the work of the League. The British Red Cross. We have approached the British Red Cross through our lay councillor, the Hon. Sir Arthur Stanley, on the subject of co-operation in health education in factories and other channels, but so far nothing has matured. 35 200/B/3/2/C693/1/71